2018
DOI: 10.3389/fpls.2018.00698
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Cell Wall-Associated Defense Responses to Infection by Sporisorium scitamineum

Abstract: The plant cell wall is known to be the first barrier against plant pathogens. Detailed information about sugarcane cell wall-associated defense responses to infection by the causal agent of smut, Sporisorium scitamineum, is scarce. Herein, (immuno)histochemical analysis of two smut resistant and two susceptible sugarcane cultivars was conducted to understand host cell wall structural and compositional modifications in response to fungal infection. Results showed that the fungus grew on the surface and infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Transcripts annotated with the lignin biosynthetic process term (GO:0009809) showed a substantial decrease in expression in the first time point after inoculation, with some reestablishment at 48 hai (Fig 2-A). Lignin deposition in the epidermis is an important event to prevent sugarcane infection by S. scitamineum at 24 hai [102]. We observed that almost all genes of cinnamyl-alcohol dehydrogenase (CAD), a precursor of lignin biosynthesis, returned to their basal expression level after marked downregulation at 12 hai.…”
Section: Wrky Transcription Factors Cell Wall Reinforcement and Stress-regulated Transcripts Altered In The First Two Days Following Inocmentioning
confidence: 93%
“…Transcripts annotated with the lignin biosynthetic process term (GO:0009809) showed a substantial decrease in expression in the first time point after inoculation, with some reestablishment at 48 hai (Fig 2-A). Lignin deposition in the epidermis is an important event to prevent sugarcane infection by S. scitamineum at 24 hai [102]. We observed that almost all genes of cinnamyl-alcohol dehydrogenase (CAD), a precursor of lignin biosynthesis, returned to their basal expression level after marked downregulation at 12 hai.…”
Section: Wrky Transcription Factors Cell Wall Reinforcement and Stress-regulated Transcripts Altered In The First Two Days Following Inocmentioning
confidence: 93%
“…The protocol established by Marques et al [37] was used to verify the presence of C. acutatum hyphae in petal and calyx tissues. The glass slides were treated with a WGA-Alexa Fluor 488 dilution according to the manufacturer (Life ® ) for 30 min and then washed in water once for 3 min.…”
Section: Fungal Detectionmentioning
confidence: 99%
“…O 2À and H 2 O 2 were visualized in situ following Jabs et al (1996) and Thordal-Christensen et al (1997), respectively. Transmission electron microscopy (Marques et al, 2018) and scanning electron microscopy (Baisakh et al, 2012) were conducted to examine chloroplast ultrastructure and stomata, respectively (Method S1). All quantitative data were analysed statistically for variance (ANOVA), and treatment means were compared by Tukey's HSD in XLSTAT add-in of Microsoft Excel.…”
Section: Phenotypic Physiological Biochemical and Microscopic Analysesmentioning
confidence: 99%